Comparing Patient-reported Outcomes to Patient Satisfaction After a Microdiscectomy for Patient's With a Lumbar Disk Herniation. Issue 2 (March 2020) - Schroeder, Gregory D.; Radcliff, Kristen E.; Vaccaro, Alexander R.; Murphy, Hamadi; Sutton, Ryan M.; Lurie, Jon D.; Zhao, Wenyan; Hilibrand, Alan S.
Abstract : Study Design: A retrospective cohort study. Objective: The objective of this study was to determine if patient satisfaction is predicted by improvement in health-related quality of life (HRQOL) metrics. Summary of Background Data: Patient satisfaction is becoming an increasingly common proxy for treatment quality; however, the correlation between patient satisfaction and HRQOL outcome metrics following a lumbar disk herniation is unclear. Methods: Patients enrolled in the Spine Patient Outcomes Research Trial (SPORT) study were prospectively enrolled at 13 institutions. A retrospective subgroup analysis of prospectively collected data from the SPORT trial was performed. Receiver operating characteristic curves were used to determine if improvement in HRQOL metrics could accurately identify patient satisfaction. HRQOL metrics included: Short Form-36 (SF-36), Oswestry Disability Index (ODI), Sciatica Bothersomeness Index, Back Pain Bothersomeness Scale, and Leg Pain Bothersomeness Scale. Results: A total of 709 patients who underwent surgery and 319 patients treated without surgery were included. In the surgical cohort, receiver operating characteristic curve analysis demonstrated that SF-36 Physical Component Summary improvement had moderate accuracy [area under the curve (AUC)=0.77 (95% confidence interval, CI: 0.73–0.82)] at predicting satisfaction at 3 months, and it had excellent accuracy at predicting satisfaction at 2 years [AUC=0.81 (95% CI: 0.77–0.85)] and 4 years [AUC=0.81 (95% CI: 0.76–0.85)]. Absolute Physical Component Summary score had excellent accuracy at 3 months [AUC=0.83 (95% CI: 0.79–0.87)], 2 years [AUC=0.87 (95% CI: 0.84–0.9)] and 4 years [AUC=0.84 (95% CI: 0.8–0.89)]. Similarly improvement in the ODI had moderate accuracy of predicting satisfaction at 3 months [AUC=0.77 (95% CI: 0.72–0.81)], 2 years [AUC=0.78 (95% CI: 0.74–0.82)] and 4 years [AUC=0.78 (95% CI: 0.73–0.83)], and the absolute ODI score had excellent accuracy at 3 months [AUC=0.85 (95% CI: 0.82–0.89)], 2 years [AUC=0.89 (95% CI: 0.86–0.92)], and 4 years [AUC=0.88 (95% CI: 0.85–0.92)]. Conclusions: HRQOL metrics can accurately predict patient satisfaction with symptoms at 3 months, 2 years, and 4 years after surgical intervention for a lumbar disk herniation. Absolute outcome scores were somewhat more predictive than change scores.